2017
DOI: 10.5433/1679-0359.2017v38n5p2995
|View full text |Cite
|
Sign up to set email alerts
|

Seed treatment for management of Meloidogyne javanica in soybean

Abstract: The objective of this study was to evaluate the efficacy of the active ingredient abamectin, either in isolation or in combination with fungicides and insecticides formulated for the industrial seed treatment, on the population of Meloidogyne javanica, tested under greenhouse and in vitro conditions. In both tests, the combination of the following treatments was assessed: abamectin; thiamethoxam; fludioxonil + metalaxyl-M + thiabendazole. Water was used as control for the in vitro assay, whereas under greenhou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Although it was not clear how long the seed remnants would continue to release cucurbitacins into the rhizosphere, in the current pea study the activity occurred as long as 60 days after inoculation with nematodes. The latter was substantially longer than the observed effects of synthetic chemical nematicides in epigeal seeds, where efficacy on nematode suppression lasted for no more than 15 days after sowing (Monfort et al, 2006;De Almeida et al, 2017). In our study, M. incognita was managed by the released cucurbitacins from seed remnants for at least 3 nematode life cycles, which was similar to situations where cucurbitacin phytonematicides were applied using GLT system (Mashela, 2002).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although it was not clear how long the seed remnants would continue to release cucurbitacins into the rhizosphere, in the current pea study the activity occurred as long as 60 days after inoculation with nematodes. The latter was substantially longer than the observed effects of synthetic chemical nematicides in epigeal seeds, where efficacy on nematode suppression lasted for no more than 15 days after sowing (Monfort et al, 2006;De Almeida et al, 2017). In our study, M. incognita was managed by the released cucurbitacins from seed remnants for at least 3 nematode life cycles, which was similar to situations where cucurbitacin phytonematicides were applied using GLT system (Mashela, 2002).…”
Section: Discussionsupporting
confidence: 69%
“…In plant nematodes, yield loss is directly proportional to the initial nematode population densities (Pi) that would infect the developing root system (Seinhorst, 1965). Thus, seed priming would be ideal for suppressing Pi as observed previously in seed dressing of cotton (Gossypium hirsutum L.), sunflower (Helianthus annuus L.), okra (Abelmoschus esculentus L.) Moenchand soybean [Glycine max (L.) Merr] with various active ingredients, primarily those of synthetic chemical nematicides such as abamectin (Monfort et al, 2006;De Almeida et al, 2017). Seed germination was previously shown to be highly sensitive to cucurbitacin phytonematicides, particularly when used as granular formulation (Martin and Blackburn, 2003;Mashela, 2009, 2010;Mazloom et al, 2009;Mafeo et al, 2011;Gautam et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Avicta® containing ABM reduced hatching and increased M. javanica J 2 mortality in vitro. In addition to the nematostatic eff ect, Avicta® possessed a nematicidal eff ect (Almeida et al, 2017). However, while studying the toxicity of EMB and ABM to M. incognita juveniles in the laboratory, Ding et al (2009) reported that the toxicity of EMB was found higher than that of ABM, their LC 50 being 0.1645 and 0.4532 mg/l, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The use of seed treatments is, however, gaining more attention, especially in Brazil where products, such as Ecolife ® , Cruiser ® , Maxim Advanced ® , Avicta ® , and other abamectin-cointaining products, have been found to reduce population densities of target species, such as M. javanica and P. brachyurus, in glasshouse and in vitro studies [85][86][87]. Another seed treatment product ILeVO ® (Bayer CropScience) that uses fluopyram as an active ingredient was registered in 2014 against sudden death syndrome and p nematode pests of soybean [88].…”
Section: Chemical Controlmentioning
confidence: 99%